A Review on Genetic Algorithm Operations and Application in Telecommunication Routing - Singh, Neha; PK, Chaurasia (International Journal of Computer Sciences and Engineering, 2019)
Genetic algorithm is a powerful tool and wide class of global optimization methods. It belongs to the large class of evolutionary algorithm and an efficient way to get optimal solutions. There is a large class of optimization problems that are quite hard to solve by conventional optimization technique but genetic algorithm (GA) is very efficient in that case too. Genetic Algorithm is used to solve many real world problems, some applications are as automotive design, Robotics, Optimized Telecommunications Routing, Biometric invention, Trip-traffic and Shipment routing, Computer gaming, Gene expression profiting, Marketing and Merchandising, etc. The main goal of this work is to solve the telecommunication routing problem by using Genetic Algorithm.